1997
DOI: 10.1099/00222615-46-7-541
|View full text |Cite
|
Sign up to set email alerts
|

Identification of heparan sulphate binding surface proteins of Helicobacter pylori: inhibition of heparan sulphate binding with sulphated carbohydrate polymers

Abstract: Heparan sulphate binding to cells of the gastric pathogen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 26 publications
2
31
1
Order By: Relevance
“…Utt and Wadström (103) confirmed that binding of heparan sulfate by H. pylori at pH 4 to 6 is very common among H. pylori strains. As the previous study had indicated, inhibitory assays with various compounds such as dextran sulfate and carrageenans revealed that inhibition was related to the sulfate content of the molecule, not to the carbohydrate polymer backbone.…”
Section: Heparin and Heparan Sulfatementioning
confidence: 52%
“…Utt and Wadström (103) confirmed that binding of heparan sulfate by H. pylori at pH 4 to 6 is very common among H. pylori strains. As the previous study had indicated, inhibitory assays with various compounds such as dextran sulfate and carrageenans revealed that inhibition was related to the sulfate content of the molecule, not to the carbohydrate polymer backbone.…”
Section: Heparin and Heparan Sulfatementioning
confidence: 52%
“…Studies have shown the presence of HSBP in H. pylori [18,19,28,45], where the interaction of these bacterial proteins with host components was exploited. It could be determined that these proteins recognised heparin, gastrointestinal cell surface HS, in an association inhibitable by the presence of sulphated carbohydrate polymers in the media.…”
Section: Discussionmentioning
confidence: 99%
“…pylori strain 25 (clinical isloate from adenocarcinoma) was provided by Professor T. Wadstro Èm (Lund University, Sweden). This strain, which has previously been examined for haemagglutinins [18] and was also found to bind HS with high af®nity [28], was selected for characterisation of HSBPs.…”
Section: Bacterial Strain and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A heparin-binding protein was located at the cell surface by biotinylation and indirect immunofluorescence assays. This protein corresponded to a 55-60 kDa molecule (Utt & Wadstrom, 1997 terial recruitment of molecules, such as heparin, in the immediate environment during the infectious process. These molecules can then serve as universal binding sites for various mammalian heparin-binding proteins.…”
Section: Introductionmentioning
confidence: 99%